2021
DOI: 10.1016/j.nicl.2021.102735
|View full text |Cite
|
Sign up to set email alerts
|

The link between gliomas infiltration and white matter architecture investigated with electron microscopy and diffusion tensor imaging

Abstract: Highlights Possible favorable factors for glioma infiltration were investigated with MRI, TEM and DTI analysis. The infiltration of white matter bundles (WMB) displayed regional differences in three gliomaś subgroups. Regional differences within the same WMB were detected by morphological (TEM) and DTI analysis. HIF regions, common to all gliomas subgroups, displayed a smaller fiber diameter, lower FA and higher RD. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 80 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…Studies on PTZ patterns of WM displacement and/or invasion may be important for understanding how much functional brain tissue is compromised, because invasion of the WM tract connectivity prior to surgery represents a main limitation of neuroplasticity [35]. Latini et al (2021), when trying to understand whether specific features of the different WM pathways could reflect the differences in observed glioma infiltration, built a theory that a smaller fiber diameter, decreased fiber density and increased extracellular space may represent pathways of least resistance for glioma cell dissemination [36]. In the same spirit, a recent review on DLGG interaction with WM tracts suggested that myelin may constitute a protection against glioma cell migration; therefore, its nonexistence or destruction could result in fragility sites facilitating tumor invasiveness [37].…”
Section: Dlgg Heterogeneity and Relation With The Surrounding Brain: ...mentioning
confidence: 99%
“…Studies on PTZ patterns of WM displacement and/or invasion may be important for understanding how much functional brain tissue is compromised, because invasion of the WM tract connectivity prior to surgery represents a main limitation of neuroplasticity [35]. Latini et al (2021), when trying to understand whether specific features of the different WM pathways could reflect the differences in observed glioma infiltration, built a theory that a smaller fiber diameter, decreased fiber density and increased extracellular space may represent pathways of least resistance for glioma cell dissemination [36]. In the same spirit, a recent review on DLGG interaction with WM tracts suggested that myelin may constitute a protection against glioma cell migration; therefore, its nonexistence or destruction could result in fragility sites facilitating tumor invasiveness [37].…”
Section: Dlgg Heterogeneity and Relation With The Surrounding Brain: ...mentioning
confidence: 99%
“…In recent years, this field has gradually shifted from exploring the relationship between macroscopic, whole-brain diffusion tensor changes and tumor progression, to exploring the relationship between local, www.nature.com/scientificreports/ microscopic fiber bundle changes and local tumor invasion. Previous work has revealed that voxels with higher RD and lower FA are associated with glioma cell infiltration 15 . Among the existing studies, only one has focused on insular glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unique anatomical location of the insular lobe, the relationship of insular glioma to surrounding fiber bundles is more complicated than that of general intracranial tumors. Using traditional imaging data, previous studies have focused on qualitative analyses of the fiber bundles that may be involved in insular tumors [13][14][15] . These studies could only assess changes in the surrounding fibers due to invasion or edema, which could not be remodeled to preserve local function; such plastic changes in white matter typically occur distal to the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 1097 cases, a tumor located in a nonfrontal area was an independent factor of poor prognosis [ 10 ]. With its invasive profile, glioma has a high propension to migrate along the subcortical fibers, as shown radiologically [ 41 , 42 ] as well as pathologically: biopsy samples evidenced that the tumor cells followed the white matter tracts and were slightly more concentrated in the peripheral parts of those tracts [ 43 ]. It seems that the myelin status could play a pivotal role not only in LGG invasion in adults but also possibly in its origin in teenagers [ 44 ].…”
Section: Predicting Oncological Interindividual Variability and Its C...mentioning
confidence: 99%